Multi-analyte liquid biopsy approaches for early detection of esophageal cancer: the expanding role of ctDNA - Tai, Derek; Latif, Kareem; Shah, Pranati; Park, Daniel; Crook, Christiana; Guzman, Sofia; Brar, Gagandeep; Li, Daneng; Castillo, Dani (Frontiers in Oncology, 2025)
Circulating tumor DNA (ctDNA) has emerged as a promising biomarker for the early detection of esophageal cancer (EC), offering a minimally invasive means to assess tumor-derived genomic and epigenomic alterations. This review synthesizes current data on ctDNA biology, detection technologies, diagnostic performance, and clinical applicability in both esophageal adenocarcinoma and squamous cell carcinoma. We conducted a comprehensive literature review of PubMed-indexed studies on ctDNA in EC, emphasizing recent (January 1, 2019– December 31, 2024) findings, systematic reviews, and meta-analyses. Key data on ctDNA characteristics, diagnostic performance in both early-stage esophageal adenocarcinoma and squamous cell carcinoma, and clinical outcomes were extracted. We also discuss technical and clinical challenges in ctDNA assays and future perspectives for integrating ctDNA evaluation into clinical practice. We highlight technological innovations such as methylation profiling, fragmentomics, and ultrasensitive sequencing, and compare ctDNA-based approaches to alternative non-endoscopic modalities. While early studies report encouraging sensitivity and specificity for ctDNA in high-risk populations, specifically with methylation assays, current data remain limited by small sample sizes, retrospective design, low tumor DNA abundance, and heterogeneity in assay methodology. Furthermore, the clinical implementation of ctDNA-based screening must address population-level feasibility, cost-effectiveness, and health equity. We conclude that ctDNA holds significant potential for early EC detection but remains investigational pending validation in large prospective cohorts.